Dakwah Ustadz Abdul Somad Pada Media Sosial Tiktok: Upaya Menjaga Adab Dalam Berkomunikasi - Meilia, Stevy Arta; Ardana, Anna Fitri; Razzaq, Abdur; Nugraha, Muhamad Yudistira (Komunika : Jurnal Ilmiah Komunikasi, 2024)
The development of digital technology has significantly influenced the way Islamic preaching is disseminated. Social media platforms, particularly TikTok, have become effective tools for delivering religious messages to a broader audience, especially the younger generation. This study aims to analyze how Ustadz Abdul Somad (UAS) utilizes the TikTok platform to convey his preaching messages. The research employs a qualitative approach using observation techniques to examine UAS's preaching content on TikTok. The findings reveal that UAS is able to present Islamic messages in a concise, engaging, and communicative manner, allowing him to reach a wider audience. Furthermore, his choice of language and rhetorical style also contributes to the appeal and effectiveness of the preaching message delivery. Keyword : Digital Preaching, Ustadz Abdul Somad, TikTok, Communication Manners, Social Media.